p53 gene mutations in skin cancers with underlying disorders - Kanekura, Takuro; Kanzaki, Tamotsu; Kanekura, Shoko; Kawahara, Kouichi; Nakashima, Toshihiro; Kitajima, Isao; Maruyama, Ikuro (Journal of dermatological science, 1995)
Mutations in p53, a tumor suppressor gene, are one of the most common genetic lesions of human cancers. The relationship between pS3 gene mutation and ultraviolet (UV) light has been demonstrated in skin cancers of sun-exposed sites. In this study, genomic DNA from 12 skin cancers was screened for mutations in exons 5 to 9 of this gene using the polymerase chain reaction — single strand conformation polymorphism (PCR-SSCP) analysis followed by DNA sequencing. DNA samples were obtained from 8 basal cell carcinomas (BCCs): 1 from an organoid nevus, 1 from a patient with basal cell nevus syndrome, 1 from a patient with xeroderma pigmentosum, and 1 from a recurrent and 4 from primary sporadic lesions on actinic damaged skin, and from 4 squamous cell carcinomas (SCCs): 1 from a burn scar, 1 from a patient with epidermodysplasia verruciformis, and 2 from actinic keratosis. Mutation of the p53 gene was detected in only 1 case of SCC which had arisen from actinic keratosis. The mutation occurred at codon 159 in exon S with a GCC to CCC base-pair substitution resulting in an amino acid change of alanine to proline. This mutation does not correspond to results of UV mutagenesis studies reported in the literature. Our findings imply that, although p53 gene mutation and UV exposure play an important role in the carcinogenesis of some skin cancers, they are not crucial, especially in skin cancers that develop from underlying skin disorders.